Improvement of translucency in Al2O3 ceramics by two-step sintering technique - Kim, Dong-Suk; Lee, Jong-Heun; Sung, Rak Joo; Kim, Sang Woo; Kim, Hyung Soo; Park, Jeong Shik (ELSEVIER SCI LTD, 2007)
Pure, 140, 500, and 2500 ppm MgO-doped Al2O3 specimens were sintered at 1700 degrees C in a vacuum with and without pre-sintering heat treatment (HT) at 800 degrees C for 50 h in air. Pre-sintering HT improved the transmittance in the visible (400-700 nm) range significantly. This enhanced transmittance was explained in terms of the removal of residual pores and the homogenization of the microstructure due to the lowering of the boundary mobility as a result of the MgO addition and the suppression of local densification through a pre-coarsening step. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ABNORMAL GRAIN-GROWTH; ALUMINA; STRENGTH